The effect of cockleshells on compressive strength of compressed sawdust concrete cube - Syarifah Aida Syafiqa, Sayed Azmi (2015)
Due to increasing cost of material in the market nowadays, there is needed to search another alternative material in order to save the cost in constructing the buildings. Sawdust had been proven to be the replacement of coarse aggregate in concrete in order to produce the lightweight concrete. However, there are some problem relate to the uses of sawdust in concrete making. The production of sawdust requires high water absorption and affects hardening time of concrete. The objective of this study is to determine the compressive strength of sawdust lightweight aggregate concrete between treated and non-treated by using lime as pre-treatment. In this study, sawdust concrete is casted using the compression method using the cinva ram. The sawdust was treated using lime before he casting work as for treated sawdust and was soaked in the water for non-treated sawdust. As to improve the brittleness of the concrete cube, soil is added to the sawdust concrete with nominal mix 1:1:0.5:2.5; (sand: cement: soil: sawdust). From the study, its shows that the non-treated sawdust concrete is having the higher strength compare to the treated sawdust concrete. Based on the result, non-treated sawdust concrete was added with cockleshell as additive material with nominal mix 1:1:0.5:2.5:0.33, 1:1:0.5:2.5:0.67, 1:1:0.5:2.5:1.00 to achieve the main objective of this study. The 28 days compressive strength sawdust concrete with nominal mix 1:1:3 were 0.938 Mpa. The treated sawdust concrete with nominal mix 1:1:3 show the lowest compressive strength 0.063 Mpa. Treated and Non-treated sawdust concrete with the addition of soil with nominal mix 1:1:0.5:2.5 for 28 days compressive strength are 0.944 Mpa and 1.064 Mpa respectively. The non-treated sawdust gives the higher compressive strength. Sawdust concrete with the addition cockleshell as an additive with nominal mix 1:1:0.5:2.5:0.33, 1:1:0.5:2.5:0.67, 1:1:0.5:2.5:1.00 for 28 days compressive strength ware 1.337 Mpa, 1.053 Mpa and 0.661 Mpa respectively. The maximum compressive strength of sawdust concrete was 1.064 Mpa for non-treated sawdust with nominal mix 1:1:0.5:2.5. These values indicate that sawdust cannot be used in concrete brick production